In Vitro Biocompatibility of Electrospun Poly(ε-Caprolactone)/Cellulose Nanocrystals-Nanofibers for Tissue Engineering. (15th October 2019) - Dutta, Sayan Deb; Patel, Dinesh K.; Seo, Yu-Ri; Park, Chan-Woo; Lee, Seung-Hwan; Kim, Jin-Woo; Kim, Jangho; Seonwoo, Hoon; Lim, Ki-Taek
Abstract : Cellulose nanocrystals (CNCs) have emerged as promising materials for the fabrication of micro/nanoplatforms that can replace tissues more effectively. CNCs offer interesting properties that facilitate the enhancement of polymer properties. Cytotoxicity of rice husk-derived CNCs was evaluated through WST-1 assay in the presence of human mesenchymal stem cells. Electrospinning technique was used to fabricate nanofibers of poly- ε -caprolactone and its composites. Significant improvement in the mechanical property was observed in the composites relative to the pure polymer. This improvement was attributed to the better interfacial interactions between the polymer matrix and CNCs. Notably, better cell viability and differentiation were observed with the composite nanofibers than with the pure polymers. The osteogenic potential of the fabricated nanofibers was assessed by alizarin red S staining and real-time PCR. Enhanced mineralization occurred in the presence of the composite rather than pure polymer nanofibers. Furthermore, the higher levels of osteogenic markers observed with the media containing the composites clearly indicated their osteogenic potential. These results suggested that fabricated composites have the potential to be used as a biomaterial for tissue engineering applications.